An evaluation of knowledge, attitude and practice of pharmacovigilance among medical students and doctors at a tertiary care hospital - Beedimani, Ravindra S.; Zaman, Sameer Uz; Darb, Subrahmanyam; Potturi, Sharat Chandra (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Drugs are one of the most commonly used interventions in medical therapeutics. Spontaneous reporting of adverse drug reactions (ADRs) is the backbone of pharmacovigilance (PV) program. Under-reporting of ADRs by prescribers was possibly due to lack of knowledge, attitude and practices regarding PV. This study was done to assess the knowledge, attitude, and practice (KAP) of medical students (grouped to sixth and eighth semester) and medical doctors about PV in a tertiary care hospital. Methods: It was a questionnaire based cross-sectional study administered to 246 medical students and doctors. Study tool was a validated questionnaire containing 15 questions to evaluate KAP of PV among medical students and doctors. A descriptive analysis of data was done where necessary, statistical significance for associations between the group and their responses to questionnaire was provided using Pearson Chi square test and Fisher exact test. Results: Sixty-eight percent of the participants (90% doctors; 76% eighth-semester and 46% sixth-semester medical students) know the correct definition of PV. Sixty-one percent of the participants (67% sixth-semester, 61% doctors and 53% eighth-semester) think that reporting is a professional obligation for them. Only 15% of the participants have ever been taught or trained on how to report an ADR. Conclusions: Medical doctors and students lack adequate knowledge and practice of reporting ADRs, but they seem to have a positive attitude towards the PV program. Our study findings strongly suggest that there is a great need to create awareness amongst them to promote reporting of ADRs.